Peningkatan Ketahanan Pangan Melalui Penguatan Kelompok Tani - Barokatuminalloh Barokatuminalloh; Neni Widayaningsih; Diah Setyorini Gunawan (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2018)
The research is based on the low household food security in Banyumas regency. One way to improve it is by empowering farmer groups. The growing group of farmers is "Minasari". focuses on the analysis of farmer group strengthening aspects. Strengths: have fish seeding certificate, access to information, training on fish feed, high confidence level. Weaknesses: low education level, unstable members, lack of response to information, marketing difficulties. Opportunities: "Minapolitan" Policy, the existence of KSU "Ngudi Rahayu"; buffer Beji Village. Threats: fishponds are narrow, depending on the weather, no follow-up after training, no bargaining position, and no cooperation with other parties.